NILAI PENDIDIKAN KARAKTER DALAM NOVEL BUKU BESAR PEMINUM KOPI KARYA ANDREA HIRATA - Lestari Sauddeinuk (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2024)
purpose of this study is to describe the moral values contained in the novel “Big Book of Coffee Drinkers” by Andrea Hirata and to describe their relationship with learning indonesia in high school. This research the object of this research is a literary work that contains many values social life in society. The data in this study are words, phrases, and sentences with the data source being the novel Big Book of Coffee Drinkers by Andrea Hirata. Data collection techniques in this study using library techniques and reading notes. While data analysis technique in this study uses content analysis techniques. To maintain the validity of the data, data triangulation activities were carried out. Based on the results of data analysis that has been carried out, several conclusions were obtained as follows, (1) three types of moral values were found in Andrea Hirata novel Big Book of Coffee Drinkers, namely moral values related to oneself, moral values related to fellow human beings, and moral values realated to God. (2) found several froms of moral values from each type of moral values, and (3) their relationship with learning indonesia inSMA class XII.